Exclusive production of pions and the pion distribution amplitude - Fagundes, D. A.; Luna, E. G.S.; Natale, A. A. [UNESP]; Peláez, M. (IOP Publishing, 2020)
Considering, as a limit case, an approximately flat pion distribution amplitude, which is determined from the hardest, in momentum space, solution of the Bethe-Salpeter equation for the pion wave function, we compute the pion transition form factor Fπγγ ∗ (Q2) and the pion form factor F π(Q 2), taking into account the LO as well as NLO form of the hard coefficient function entering the leading-twist factorization formula. We also compute the exclusive photoproduction of pions pairs at high energies, γγ →π+π-, where perturbative QCD can be used to compute the hard scattering matrix elements. We verify that the existent data for exclusive pion production can be reasonably described as a function of such a flat distribution amplitude.
Keywords: non-perturbative QCD; pion distribution amplitude; pion transition form factor